Hypothalamic–pituitary–adrenal axis activation and glucocorticoid‐responsive gene expression in skeletal muscle and liver of Apc mice. Issue 3 (11th March 2022) - Martin, Agnès; Castells, Josiane; Allibert, Valentine; Emerit, Andréa; Zolotoff, Cindy; Cardot‐Ruffino, Victoire; Gallot, Yann S.; Vernus, Barbara; Chauvet, Véronique; Bartholin, Laurent; Schaeffer, Laurent; Durieux, Anne‐Cécile; et al.
Abstract: Background: Cancer patients at advanced stages experience a severe depletion of skeletal muscle compartment together with a decrease in muscle function, known as cancer cachexia. Cachexia contributes to reducing quality of life, treatment efficiency, and lifespan of cancer patients. However, the systemic nature of the syndrome is poorly documented. Here, we hypothesize that glucocorticoids would be important systemic mediators of cancer cachexia. Methods: To explore the role of glucocorticoids during cancer cachexia, biomolecular analyses were performed on several tissues (adrenal glands, blood, hypothalamus, liver, and skeletal muscle) collected from Apc Min/+ male mice, a mouse model of intestine and colon cancer, aged of 13 and 23 weeks, and compared with wild type age‐matched C57BL/6J littermates. Results: Twenty‐three‐week‐old Apc mice recapitulated important features of cancer cachexia including body weight loss (−16%, P  < 0.0001), muscle atrophy ( gastrocnemius muscle: −53%, P  < 0.0001), and weakness (−50% in tibialis anterior muscle force, P  < 0.0001), increased expression of atrogens (7‐fold increase in MuRF1 transcript level, P  < 0.0001) and down‐regulation of Akt–mTOR pathway (3.3‐fold increase in 4EBP1 protein content, P  < 0.0001), together with a marked transcriptional rewiring of hepatic metabolism toward an increased expression of gluconeogenic genes ( Pcx : +90%, Pck1 : +85%), and decreased expression of glycolytic ( Slc2a2 : −40%, Gk : −30%, Pklr : −60%), ketogenic ( Hmgcs2 : −55%, Bdh1 : −80%), lipolytic/fatty oxidation ( Lipe : −50%, Mgll : −60%, Cpt2 : −60%, Hadh : −30%), and lipogenic ( Acly : −30%, Acacb : −70%, Fasn : −45%) genes. The hypothalamic pituitary–adrenal axis was activated, as evidenced by the increase in the transcript levels of genes encoding corticotropin‐releasing hormone in the hypothalamus (2‐fold increase, P  < 0.01), adrenocorticotropic hormone receptor (3.4‐fold increase, P  < 0.001), and steroid biosynthesis enzymes ( Cyp21a1, P  < 0.0001, and Cyp11b1, P  < 0.01) in the adrenal glands, as well as by the increase in corticosterone level in the serum (+73%, P  < 0.05), skeletal muscle (+17%, P  < 0.001), and liver (+24%, P  < 0.05) of cachectic 23‐week‐old Apc mice. A comparative transcriptional analysis with dexamethasone‐treated C57BL/6J mice indicated that the activation of the hypothalamic–pituitary–adrenal axis in 23‐week‐old Apc Min/+ mice was significantly associated with the transcription of glucocorticoid‐responsive genes in skeletal muscle ( P  < 0.05) and liver ( P  < 0.001). The transcriptional regulation of glucocorticoid‐responsive genes was also observed in the gastrocnemius muscle of Lewis lung carcinoma tumour‐bearing mice and in KPC mice ( tibialis anterior muscle and liver). Conclusions: These findings highlight the role of the hypothalamic–pituitary–adrenal‐glucocorticoid pathway in the transcriptional regulation of skeletal muscle catabolism and hepatic metabolism during cancer cachexia. They also provide the paradigm for the design of new therapeutic strategies.